ANALISIS STRES KERJA DAN KOMPENSASI TERHADAP INTENSI KELUAR KARYAWAN BAGIAN PENJUALAN PT BUDI BERLIAN PRINGSEWU - Puspita Cahyaningsih; Nur Efendi; Hani Damayanti Aprilia (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
Analysis of Job Stress and Compensation to Turnover Intention of Employee Marketing Division PT Budi Berlian Motor Pringsewu Abstract This study aims to determine the influence of work stress and compensation on the intention to leave PT Budi Berlian Motor Pringsewu. This study uses a quantitative approach with saturated sampling technique as a sampling technique. The sample in this study were employees of the sales department as many as 30 respondents. Data collection through questionnaires and data analysis used is multiple linear regression analysis. Based on the results of data analysis, it shows that job stress and compensation partially and simultaneously have a significant effect on turnover intention. The highest factor affecting intention to leave is compensation. To control the intention to leave employees, it is advisable for companies to maintain the compensation policy that has been implemented. Keyword: Job Stress, Compensation, and Turnover Intention